Observations on Michigan Indians - Bosin, John; Burrows, Edwin; Bush, Frank; Bush, John; Deyo, Rodney; Fulton, Ann; Fulton, Bruce; Fulton, Douglas; Lacasse, Fred; McCarus, Ernest; Neyome, Jack; Pamp, Betty; et al. (1953)
The first section (Series I) of this recording collection consists of 13 episodes of the radio program "Red Man in Michigan," broadcast on WUOM radio in Ann Arbor, Michigan. These programs use extensive clips from field recordings made by Gertrude Prokosch Kurath, and cover a wide range of historical and contemporary topics directed to a general non-Native audience. Series II consists of tapes including Ottawa language hymns from a series of programs titled "Comparisons of Chippewa Revival Hymns, Michigan and Ontario, 1953-1962"; interviews on the organization of United Church, on the organization of Camp Meetings, on missionary experiences, especially at Perry Island and Moose Point, Ontario; recordings of powwows at Ann Arbor, Lansing, and Hastings, including some Kiowa performances by John Bosin; an interview with Jim Eagle Shaffer; and an interview with Anna Fulton, Douglas Fulton, and Bruce Fulton on socio-economic conditions and racial discrimination against Native people in Michigan.